MAKNA IMPERATIF PADA TUTURAN IMPERATIF DALAM TEKS CERITA RAKYAT TURI-TURIAN SI JONAHA - Johan Siregar; Elmustian Rahman; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:The meaning of imperative is the purpose, objective or desire of speakers contained in an imperative speech. The imperative meaning is found in many forms of imperative speech and in various forms of meaning. The form of imperative speech is imperative construction based on formal structure. In a culture of society there must be a culture that is well known, both within the cultural environment of society itself and also other people's cultural environment, that’s how Batak Toba community creates its own cultural results. Batak Toba Community is a community which is living in North Sumatra that has a hard character and firm, both in behaving and speaking. Batak Toba community has many cultural results, one of cultural literatures known as folklore is Turi-Turian Si Jonaha. With exclusive character of Batak Batak community, the folklore of Turi-Turian Si Jonaha has many imperative speech in various forms in it. This study used a qualitative approach with the type of research was descriptive qualitative oriented to pragmatic theory. In addition to pragmatic theory, context was also used to analyze imperative speech contained in Turi-Turian Si Jonaha folklore. The number of imperative speech in the folklore Turi-Turian Si Jonaha brought this research focusing on the form of imperative construction itself. The result of this research indicates that 91 imperative speech were found and then analyzed and classified grounded on implicit meanings in this imperative itself. After being analyzed and classified, there were 14 types of imperative meaning found such as imperative of order, imperative of message, imperative of demanding, imperative of adjuration, imperative of exhortation, imperative of persuasion, imperative of appeal, imperative of invitation, imperative of permission, imperative of permitting, imperative of prohibition, imperative of hope, imperative of curse and imperative of suggestion.Keywords: imperative meaning, imperative speech, folklore